Una aproximación a las emociones positivas generadas en las relaciones intergeneracionales: principales determinantes que inciden en la felicidad y bienestar de los mayores - Martínez-Martínez, Antonio Luis (2019)
There is extensive literature on the positive effects of intergenerational relationships for both older people and young people. However, in very few cases evidence of the benefits of this type of relationships beyond the integrated effect of support social networks has been presented. This study aims to elucidate the effect of the existence of family intergenerational relationships in the state of happiness of people over 65 in Spain. To do this, we used the CIS 3109 Barometer of September 2015, in order to analyze the effect of relationships and coexistence with family members under 35 years in the happiness of the elderly, both in isolation, and in combination with other variables. The results show that cohabiting or having relationships with people under 35 does not have a significant effect on the happiness of the elderly. Factors such as gender, marital status, socioeconomic status and, above all, health, have a greater impact on the scale of perceived happiness.